2014
DOI: 10.1530/jme-14-0062
|View full text |Cite
|
Sign up to set email alerts
|

RECENT RESEARCH ON THE GROWTH PLATE: Mechanisms for growth plate injury repair and potential cell-based therapies for regeneration

Abstract: Injuries to the growth plate cartilage often lead to bony repair, resulting in bone growth defects such as limb length discrepancy and angulation deformity in children. Currently utilised corrective surgeries are highly invasive and limited in their effectiveness, and there are no known biological therapies to induce cartilage regeneration and prevent the undesirable bony repair. In the last 2 decades, studies have investigated the cellular and molecular events that lead to bony repair at the injured growth pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 133 publications
3
55
0
1
Order By: Relevance
“…This indicates that deregulation in early stages of development, due to a lack of Acvr1 expression, possibly cannot be compensated later. This is in accordance with studies showing that the height of the proliferative zone during endochondral ossification already determines the longitudinal growth potential of long bones . In another mouse model, which used a Col2‐specific KO of Acvr1 , limiting its deficiency to chondrocytes, it was observed that even though all five digits were developing, their ossification was delayed .…”
Section: Discussionsupporting
confidence: 90%
“…This indicates that deregulation in early stages of development, due to a lack of Acvr1 expression, possibly cannot be compensated later. This is in accordance with studies showing that the height of the proliferative zone during endochondral ossification already determines the longitudinal growth potential of long bones . In another mouse model, which used a Col2‐specific KO of Acvr1 , limiting its deficiency to chondrocytes, it was observed that even though all five digits were developing, their ossification was delayed .…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, angiogenesis plays a crucial role during the healing process of bone fractures and growth plate injuries4142. Therefore, identifying new angiogenic factors may facilitate the development of new therapeutic treatments for skeletal pathologies and injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The GP likely becomes independent from the IPFP after ~P8 (due both to the intervening presence of the secondary ossification center as well as to cessation of Igf1 expression in the fat pad), which could also explain why it takes longer for bone growth to be significantly impaired when the injury is induced at P14 vs. P1. Finally, we cannot exclude the possibility that the IPFP and/or other local tissues hosting cells with osteochondrogenic potential, such as the synovium, bone marrow or the perichondrial groove of Ranvier (Hindle et al, 2017; Yang et al, 2013; Karlsson et al, 2009; Chung and Xian, 2014), can contribute to bone growth not only with paracrine signals, but also with progenitor cells (see for example Fig. S9 in [Yang et al, 2013]), such that cell death within these tissues in Pit::DTR mice depletes a pool of cells that participates in recovery of the injured bones.…”
Section: Discussionmentioning
confidence: 99%